Real-World Use of Clopidogrel and Ticagrelor in Patients With Myocardial Infarction With Nonobstructive Coronary Arteries: Patient Characteristics and Long-Term Outcomes - Gao, Side; Xu, Haobo; Huang, Sizhuang; Yuan, Jiansong; Yu, Mengyue (Frontiers in Cardiovascular Medicine, 2021)
Background: Current guidelines recommend ticagrelor as the preferred P2Y12 inhibitor on top of aspirin in patients after an acute coronary syndrome. Yet, the efficacy and safety of ticagrelor versus clopidogrel in patients with myocardial infarction with nonobstructive coronary arteries (MINOCA) remain uncertain. Methods: A total of 1091 patients with MINOCA who received dual antiplatelet therapy were enrolled and divided into the clopidogrel (n=878) and ticagrelor (n=213) groups. The primary efficacy endpoint was a composite of major adverse cardiovascular events (MACE), including all-cause death, nonfatal MI, stroke, revascularization, and hospitalization for unstable angina or heart failure. The safety endpoint referred to bleeding events. The Kaplan-Meier, propensity score matching (PSM), and Cox regression analyses were performed. Results: The incidence of MACE was similar for clopidogrel- and ticagrelor-treated patients over the median follow-up of 41.7 months (14.3% vs. 15.0%; p=0.802). The use of ticagrelor was not associated with a reduced risk of MACE compared with clopidogrel after multivariable adjustment in overall (HR=1.25, 95% CI: 0.84-1.86, p=0.262) and in subgroups of MINOCA patients. Further, there was no significant difference in the risk of bleeding between two groups (HR=1.67, 95% CI: 0.83-3.36, p=0.149). After PSM, 206 matched pairs were identified, and the differences between clopidogrel and ticagrelor for ischemic endpoints and bleeding events remained nonsignificant (all p>0.05). Conclusions: In this observational analysis of MINOCA patients, ticagrelor was not superior to clopidogrel in reducing ischemic events and did not cause a significant increase in bleeding, indicating a similar efficacy and safety between clopidogrel and ticagrelor. A randomized study of ticagrelor versus clopidogrel in this specific population is needed.